2010
DOI: 10.1002/ccd.22434
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter registry of 0.010‐inch guidewire and compatible system for chronic total occlusion: The PIKACHU registry

Abstract: The PIKACHU registry data suggest that the 0.010-inch system is safe and practicable for treatment of CTO lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…According to the information gleaned from both histopathological examinations and animal CTO model research, angiographically occluded lesions might possibly contain loose tissue segments in both short-duration CTO as well as old CTO (8,11). Matsukage et al (13) reported that an intermediate-stiffness, 0.010-inch wire successfully crossed approximately 70% of CTO cases in the PIKACHU (Prospective Multicenter Registry of IKAzuchi-X for CHronic Total OcclUsion) trial; hence, these results might support the existence of loose tissue segments inside CTO. If the wire tip can be controlled and directed so that it will not penetrate hard atherosclerotic plaque, the wire will automatically advance with tracking in the loose tissue segments (Fig.…”
Section: Wire Techniques With Understanding Of Cto Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the information gleaned from both histopathological examinations and animal CTO model research, angiographically occluded lesions might possibly contain loose tissue segments in both short-duration CTO as well as old CTO (8,11). Matsukage et al (13) reported that an intermediate-stiffness, 0.010-inch wire successfully crossed approximately 70% of CTO cases in the PIKACHU (Prospective Multicenter Registry of IKAzuchi-X for CHronic Total OcclUsion) trial; hence, these results might support the existence of loose tissue segments inside CTO. If the wire tip can be controlled and directed so that it will not penetrate hard atherosclerotic plaque, the wire will automatically advance with tracking in the loose tissue segments (Fig.…”
Section: Wire Techniques With Understanding Of Cto Histopathologymentioning
confidence: 99%
“…However, it is not clear which tipstrength wire should be selected for this loose tissue tracking, because each case has a different degree of tissue rigidity. In the PIKACHU trial, loose tissue tracking was performed with only a 1.0-g tip-strength hydrocoated wire (13). Although it is a reasonable strategy not to use a stiff wire that could potentially penetrate the plaque easily as a primary wire, aspects of wire handling and movement in loose tissue tracking are similar to those of acute myocardial infarction cases, in that the wire is advanced easily and smoothly, only with multiple rotations of the wire tip (Online Video 1).…”
Section: Wire Techniques With Understanding Of Cto Histopathologymentioning
confidence: 99%
“…0.010") Francesco Burzotta et al, Radial approach for CTO PCI guidewires (and balloons) [15]. The first series of such devices is represented by the "Slender System" (Japan Lifeline) and 2 studies reported their use in the setting of CTO [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The success rate was 68% of lesions treated only with 0.010 system from the antegrade approach, whereas 86% of lesions were successfully treated using any devices including the 0.014 system. The 68% success rate was notable only from the antegrade approach [24].…”
Section: In Guidewire and Compatible Balloon Systemmentioning
confidence: 98%